Application of K-Means Clustering on the Performance Evaluation of Lecturers Based on Student Questionnaire: Application of K-Means Clustering on the Performance Evaluation of Lecturers Based on Student Questionnaire - Mutiara Mala Khairunnisa; Agung Triayudi; Endah Tri Esti Handayani (Jurnal Mantik, 2020)
In the world of lectures or universities, conducting performance appraisals needs to be applied to assess the performance of lecturers. The basis used in the assessment uses the basic tri dharma of tertiary institutions. In assessing performance, data is needed related to student satisfaction with the lecturer. The data used in this study are 152 National University student satisfaction data for all lecturers of the Faculty of Communication and Information Technology at the National University, amounting to 28 lecturers. In collecting data using a questionnaire available on the National University Lecture website. There are 10 questions that need to be filled out by all active students in the 2016/2017 school year odd and even semester. Data will be processed by clustering the performance of lecturers in the cluster is good, good enough or less.